2021
DOI: 10.3389/fpls.2021.636339
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding Defense Mechanisms in Persea americana Against Phytophthora cinnamomi

Abstract: Avocado (Persea americana) is an economically important fruit crop world-wide, the production of which is challenged by notable root pathogens such as Phytophthora cinnamomi and Rosellinia necatrix. Arguably the most prevalent, P. cinnamomi, is a hemibiotrophic oomycete which causes Phytophthora root rot, leading to reduced yields and eventual tree death. Despite its’ importance, the development of molecular tools and resources have been historically limited, prohibiting significant progress toward understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 146 publications
0
15
0
Order By: Relevance
“…The molecular basis of P. cinnamomi resistance in avocado has been the topic of a recent discussion (van den Berg et al, 2021 ). This review provided an up-to-date justification and classification of avocado rootstocks as resistant, partially resistant, tolerant, or susceptible to P. cinnamomi .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular basis of P. cinnamomi resistance in avocado has been the topic of a recent discussion (van den Berg et al, 2021 ). This review provided an up-to-date justification and classification of avocado rootstocks as resistant, partially resistant, tolerant, or susceptible to P. cinnamomi .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, avocados have gained popularity because of their nutritional profile coupled with numerous health benefits associated with their consumption (Hurtado-Fernández et al, 2018 ). However, the production of avocado is severely threatened by the persistence of several pathogens in major avocado-growing regions of the world (van den Berg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds also participate in the lignification of cell walls, an additional defensive response to pathogens [ 37 ]. Lignin enrichment of root cell walls has been reported as a plant-defensive response in the early stages (hours) after infection, although, in susceptible plants, it is not sufficient to stop pathogen hyphae from penetrating into the roots [ 70 , 71 ]. It has been reported that coniferyl aldehyde is used by plants for the hydroxylation of the enzyme ferulate-5-hydroxylase as a downstream substrate in the lignin pathway [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phytophthora cinnamomi is one of the most aggressive tree pathogens in the world, and as such it is usually able to penetrate and colonize the roots of more than 5,000 host plant species, regardless of their level of susceptibility ( Shearer et al, 2007 ; Allardyce et al, 2012 ; Hardham and Blackman, 2018 ; Camisón et al, 2019 ). Plant defense response in tolerant tree species tends to be based on stopping the progress of the pathogen within the host’s tissues and/or replacing the dead roots fast enough ( Moreira and Martins, 2005 ; van den Berg et al, 2021 ). In agreement with these reports, within 36 hpi, the roots of both Q. suber and Q. variabilis developed necrotic tissue ( Figure 1C ).…”
Section: Discussionmentioning
confidence: 99%